Peripheral neuropathy associated with erythrophagocytic lymphohistiocytosis. Issue 2 (February 1988) - Boutin, B; Routon, M C; Rocchiccioli, F; Mayer, M; Leverger, G; Robain, O; Ponsot, G; Arthuis, M
Abstract : A 12 year old patient who developed clinical, biochemical and histological features of erythrophagocytic lymphohistiocytosis is described. In contrast to previously reported cases, the prominent neurological feature was a subacute sensorimotor polyneuropathy. Sural nerve biopsy showed a marked reduction of myelinated fibres and severe axonal lesions, absence of histiocyte infiltration and deposits of IgM along the epineurium. In addition to the hypertriglyceridaemia previously described in this condition, an elevation of plasma very long-chain fatty acids and phytanic acid was found which suggests a transient impairment of peroxisomal functions.